Motivation Crowding Theory: A Survey of Empirical Evidence - Bruno S. Frey; Reto Jegen (Center for Economic Studies and ifo Institute (CESifo), 2000)
The motivation crowding effect suggests that an external intervention via monetary incentives or punishments may undermine (and under different indentifiable conditions strengthen) intrinsic motivation. As of today, the theoretical 1033 possibility of crowding effects is widely accepted among economists. Many of them, however, have been critical about its empirical relevance. This survey shows that such scepticism is unwarranted and that there exists indeed compelling empirical evidence for the existence of crowding out and crowding in. It is based on circumstantial insight, laboratory studies by both psychologists and economists as well as field research by econometric studies. The presented pieces of evidence refer to a wide var iety of areas of the economy and society and have been collected for many different countries and periods. Crowding effects thus are an empirically relevant phenomenon, which can, in specific cases, even dominate the traditional relative price effect.
Keywords: 330; Crowding effect; intrinsic motivation; principal-agent theory; economic psychology; experiments